2005
DOI: 10.1002/pdi.732
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of continuous subcutaneous insulin infusion in hypoglycaemia-prone type 1 diabetes

Abstract: • The effectiveness of CSII has been poorly studied in hypoglycaemiaprone type 1 diabetic subjects, though they are prime candidates for insulin pump therapy • We found that HbA1c improved on CSII compared to MDI (including glargine) to a greater extent than expected from previous studies • We recommend that type 1 diabetic patients with frequent unpredictable hypoglycaemia during MDI should be included in NICE guidelines for CSII

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Three studies were conducted in the UK. [138][139][140] Other studies were set in Australia, New Zealand, Canada and Israel.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were conducted in the UK. [138][139][140] Other studies were set in Australia, New Zealand, Canada and Israel.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A few studies reported identical educational and support programmes for both CSII and MDI groups. [Cersosimo et al 2002, 169 Pickup et al 138 and Garcia-Garcia et al)]. 167,168 Several studies described intensive training/ education of participants and their families.…”
Section: Education and Support For Csiimentioning
confidence: 99%
See 2 more Smart Citations
“…The constancy of the basal delivery allows for a near-flat blood insulin profile, adjustable at preset times to suit the changing needs of the patient throughout the day. The controlled delivery of small insulin amounts substantially reduces glycemic variability (6,7). For many years, these advantages have allowed a superiority of insulin pump therapy over insulin injection regimens, at least as far as the frequency of hypoglycemia is concerned.…”
mentioning
confidence: 99%